Effectiveness of ethanol extract of Morinda citrifolia L. as an anti-inflammatory: A preclinical study - Mega Hayati; Ali Napiah Nasution; Ermi Girsang; Adek Amansyah; Fioni (Jurnal Teknologi Laboratorium)
The inflammatory response is triggered by infections or tissue damage, often requiring effective anti-inflammatory treatments. Morinda citrifolia L. (noni fruit) contains bioactive compounds such as flavonoids, steroids, and triterpenoids with potential anti-inflammatory properties. The aims of this research to evaluate the anti-inflammatory effects and optimal dosing of ethanol extract of noni fruit in reducing paw edema and improving histopathological conditions in male rats induced with Complete Freund's Adjuvant (CFA). This experimental study involved 30 male rats divided into six groups: normal control, negative control (CFA-only), positive control (triamcinolone 0.72 mg), and three treatment groups receiving noni fruit extract (150, 300, 600 mg/200 g BW). Edema volume was measured using a plethysmometer, and histopathological analysis of joint tissues was conducted. Noni fruit extract significantly reduced edema volume, with 600 mg/200 g BW being the most effective dose. However, histopathological analysis revealed persistent inflammatory cell infiltration and synovial hyperplasia in treated groups, indicating incomplete tissue repair compared to triamcinolone. Ethanol extract of noni fruit demonstrates significant anti-inflammatory effects, particularly at higher doses, but is less effective than triamcinolone in resolving tissue inflammation.